Benefit-cost analysis of environmental projects: A plethora of systematic biases - Philip E. Graves (Center for Economic Studies and ifo Institute (CESifo), 2010)
There are many reasons to suspect that benefit-cost analysis applied to environmental policies will result in policy decisions that will reject those environmental policies. The important question, of course, is whether those rejections are based on proper science. The present paper explores sources of bias in the methods used to evaluate environmental policy in the United States, although most of the arguments translate immediately to decision-making in other countries. There are some 'big picture' considerations that have gone unrecognized, and there are numerous more minor, yet cumulatively important, technical details that point to potentially large biases against acceptance on benefit-cost grounds of environmental policies that have true marginal benefits greater than true marginal costs, both in net present value terms. It is hoped that the issues raised here will improve future conduct of benefit-cost analyses of environmental policies.
Keywords: C91; D12; D61; D62; D78; D81; H11; H41; H43; Q20; Q30; Q51; Q58; 330; benefit-cost analysis; environmental policy; decision making; choice behavior; public goods; willingness-to-pay; willingness-to-accept; precautionary principle; hedonic methods; sum of specific damages; health effects model; environmental perceptions; Umweltpolitik; Kosten-Nutzen-Analyse; Entscheidung bei Unsicherheit; Bias; USA